Correlation of illegal addition risk and characteristics of online efficacy-claim food - LIU Mei; SU Yan; WEN Quan; HE Shaozhi; ZHOU Jia; MIN Yuhang; LI Shucai; YU Xiaoqin (Zhongguo shipin weisheng zazhi)
ObjectiveTo summarize typical situations of illegal addition， the illegal drug addition to ordinary food sold online that claimed to reduce weight was investigated， and its typical external characteristics analyzed.MethodsHigh throughput screening method and liquid chromatography tandem mass spectrometry method that could detect multiple types of compounds simultaneously and quantification accurately were developed. The packaging information， typical ingredients， gifts， production enterprises， and other external typical characteristics of the product were sorted out， and the correlation between detection results and external typical characteristics was analyzed.Results22.09% （19/86） of the weight loss claiming samples purchased online added drugs， and the drug addition behavior showed characteristics such as escape addition， combination addition， and main and auxiliary addition. There were certain correlations between drug addition and external typical features. Typical ingredients， gifts， trial products， products involving OEM， and products labeled with liability insurance had a higher probability of drug addition.ConclusionTypical situations analysis and summarization that are prone to illegal addition ， and we expected to give consumers moderate consumption advices and provide precise guidance for the regulation of illegal added products.